1988
DOI: 10.1111/j.1600-0749.1988.tb00420.x
|View full text |Cite
|
Sign up to set email alerts
|

Photo‐Induced Events in the Human Melanocytic System: Photoaggression and Photoprotection

Abstract: The human skin is submitted to solar, essentially ultraviolet radiation (UVR), aggressions, and develops, for sufficient doses, erythema and pigmentation. The individual sun-sensitivity depends on the nature and the quantity of melanins present in the epidermis. These parameters are inherited as genetic traits which account for the large variations of the constitutive and adaptive pigmentation encountered in the caucasian populations. From red-haired skin-sensitive individuals, to dark-haired sun-resistant ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…For geographical location, France was arbitrarily divided into North and South areas using the northern frontier of Aquitaine, Limousin, Auvergne, and Rhône-Alpes regions. In addition, skin phototype was determined at baseline according to the classification proposed by Césarini: I, II, IIIa, IIIb, IV, V, VI [27]. Levels I and VI, which were rare in our population, have been grouped with levels II and V respectively.…”
Section: Methodsmentioning
confidence: 99%
“…For geographical location, France was arbitrarily divided into North and South areas using the northern frontier of Aquitaine, Limousin, Auvergne, and Rhône-Alpes regions. In addition, skin phototype was determined at baseline according to the classification proposed by Césarini: I, II, IIIa, IIIb, IV, V, VI [27]. Levels I and VI, which were rare in our population, have been grouped with levels II and V respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The wide range of susceptibility to solar exposure among phototypes (Table 1) largely corresponds with two types of melanin produced by melanocytes: eumelanin (dark brown-black) and phaeomelanin (yellow-red) (Hönigsmann et al 1986;Césarini 1988;Young 1994Young , 2004. Phaeomelanin absorbs UVR photons and with overexposure produces reactive oxygen species (ROS) which are phototoxic (Fitzpatrick and Szabo 1983).…”
Section: Acute Effects On the Skinmentioning
confidence: 98%
“…Studies on purified eumelanin and pheomelanin showed that irradiation of pheomelanin results in the generation of hydroxyl radicals and superoxide anions that might contribute to oxidative DNA damage. Additionally, pheomelanin increases the release of histamine, which contributes to the sun‐induced erythema and edema in fair skinned individuals (49). Exposure of the skin to UV reduces the levels of glutathione reductase, which is important for pheomelanin synthesis, and is more prevalent in light‐colored than in dark skin (50–52).…”
Section: Comparison Of the Photoprotective Capacities Of Eumelanin Anmentioning
confidence: 99%